Wykorzystanie modelu DCC-GARCH oraz funkcji powiązań FGM w analizie zależności między stopami zwrotu z akcji, indeksów giełd światowych oraz kursami walut : przykład empiryczny - Papla, Daniel; Piontek, Krzysztof (Using DCC-GARCH model and a FGM copula in the analysis of the dependency between returns of stocks, world stock markets indexes and exchange rates : empirical example, 2006)
Main goal of this paper is an analysis of the estimation of parameters of Farlie—Gumbel Morgenstem copula (FGM) for data filtered with dynamic conditional correlation (DCC) of Engle [3], Such an estimation can help establishing a nature of dependency between time series. The paper consist of three main parts. The first part presents DCC model used for modeling a linear correlation. Also copula functions are presented here with example - multidimensional FGM copula. Data and methodology are described in second part, results - in third.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 376-383